Strategy of Indonesian Pesantren University in Achieving Competence of Student: A Grounded Research at UNIDA Gontor - Fahmy Zarkasyi, Hamid; Mas'ud, Fuad; Agung Hidayatullah, Rakhmad; Khakim, Usmanul (KnE Social Sciences, 2024)
The integration of the formal education system of higher education and pesantren the University of Darussalam (UNIDA) Gontor necessitates the attainment of distinctive student competencies. The question that arises is: how is UNIDA Gontor’s strategy in achieving student competence? Therefore, this research aims to conceptualize UNIDA Gontor’s strategy for achieving student competence. This research is field research with qualitative data, specifically using a grounded study approach. Data sources were obtained through interviews, observations, and various other documentation. The findings of this research are: First, the strategy is carried out by UNIDA Gontor by preparing daily, weekly, monthly, semesterly, and annual coaching programs. Second, the programs focus on thinking, spiritual, sport, and art exercises. Third, coaching with the ‘learning-by-doing’ method. Fourth. The coaching program is based on the values and philosophy of pesantren life. This research aims to generate theoretical conclusions regarding Islamic Human Resource Development (I-HRD) will emerge, which have implications for building pesantren management as a typical Indonesian educational institution in general, and especially pesantren universities, which are currently growing in Indonesia. Keywords: islamic human resource development (I-HRD), management of pesantren, pesantren university, UNIDA gontor; competence of student